DAPUR, MAKANAN, DAN RESISTENSI PEREMPUAN DALAM CERITA PENDEK KUTUKAN DAPUR KARYA EKA KURNIAWAN - Rusdiarti, Suma Riella (JURNAL ILMU BUDAYA, 2019)
Food and culinary has become a subject that has recently been discussed in the study of literature and popular culture. Food and culinary is not just about the fulfillment of primary needs of human, satisfy hunger and thirst, but also deals with social practices, lifestyle, identity, and even ideology. This paper will discuss food and culinary in relation to women's resistance in Eka Kurniawan’s short story entitled Kutukan Dapur (Curse of the Kitchen).  This short story tells the character Maharani who learned a lot about food, culinary, and power relations after visiting a museum. The method used is a structural study of narratology that is deepened with Pierre Bourdieu's concepts of field, power struggle, and capital. the reading of the structure of the text shows that there are two parallel narratives representing the present time and the past. The present time tells the story of Maharani who is trapped in the marriage life that is holding her back, while the past  presents the story of Diah Ayu who is intelligent and admired for her cooking skills and rebellion. The results of the analysis show that through focalisation of Maharani, the kitchen as a domestic space that is identical to the limitations of the women’s world, can turn into a field for women's resistance to reach power.